DISSEMINATING INFORMATION ON COVID-19 TO RURAL DWELLERS THROUGH TRANSLATION: A PANACEA TO COVID-19 SPREAD - Ndukauba, Kate; Nkechi B. Ohaike, (IJRDO - Journal of Social Science and Humanities Research, 2020)
The ravaging coronavirus has been declared a pandemic by the World Health Organization (WHO). Its rate of spread and mortality is alarming. To worsen matters, there is no cure, no vaccine presently, though clinical trials are going on. The economies of different countries have been shut down; people are being isolated and quarantined. Everybody has been advised to stay home and stay safe. For developing countries like Nigeria, the only safeguard to mitigate the crazy impact of the pandemic is to adhere to the precautionary measures outlined by health experts – physical distancing, wearing of facemasks, use of sanitizers, maintaining personal hygiene and avoiding social gatherings. Information on COVID-19 needs to reach all Nigerians no matter their location or level of literacy if the impact would be mitigated. Nigeria is a multilingual society so the COVID-19 information needs to be available to all linguistic groups especially those in the rural areas. This paper discusses the dissemination of information on COVID-19 to rural dwellers through translation. The focus here is the Igbo in the South Eastern part of Nigeria. The paper examines translation and terminology, then goes on to give the Igbo version of about 117 COVID-19 terms employing different methods of term creation like equivalence, composition, naturalisation, idiomatic expressions and explicative modulation. With these, the rural Igbo speakers can understand what COVID-19 is all about, the inherent dangers and the precautionary measures to take in order to stem the tide and preserve lives. Some recommendations were also made to help the containment of the pandemic.